Stratification of risk groups according to survival after recurrence in endometrial cancer patients. Issue 21 (May 2017) - Shim, Seung-Hyuk; Kim, Dae-Yeon; Kim, Hyun Jung; Lee, Shin-Wha; Park, Jeong-Yeol; Suh, Dae-Shik; Kim, Jong-Hyeok; Kim, Yong-Man; Kim, Young-Tak; Nam, Joo-Hyun
Abstract : Abstract: To identify prognostic factors for overall survival after recurrence (OSr) in endometrioid endometrial cancer (EC) patients and categorize patient subgroups that predict outcomes using these variables. Consecutive patients with recurrent endometrioid EC seen in our institution from 1989 to 2013 were retrospectively reviewed. Cox regression models were used to identify the clinicopathological factors associated with OSr. By summing scores proportionate to the hazard ratio (HR) for each significant variable, we stratified patients into 3 risk groups. Enrolled patients (n = 108) had a median time to recurrence of 15 (range, 3–163) months after initial treatment and a median OSr of 22 (range, 1–207) months. Twenty patients (18.5%) had locoregional recurrence, and 88 (81.5%) distant. One hundred three patients underwent salvage therapy; 51 (47.2%) received chemotherapy only, 22 (20.3%) received radiotherapy either alone or combined with chemotherapy, and 29 (26.9%) underwent salvage cytoreductive surgery. Multivariate regression analysis revealed that time to relapse after initial treatment, cancer antigen-125 level at recurrence, and the number of recurrent lesions were independent predictors of OSr. Incorporating these factors, we stratified patients into low-risk (n = 19), intermediate-risk (n = 43), and high-risk (n = 46) groups. The likelihood of cancer-specific death was higher in both the high-risk (HR = 8.948, 95% confidence interval [CI] = 3.498–22.893, P  < .001) and the intermediate-risk (HR = 2.619, 95% CI = 1.002–6.850, P  = .05) groups compared with the low-risk group. Incorporating 3 variables, recurrent endometrioid EC patients with a broad spectrum of outcome could be stratified according to OSr. This model may help predict outcomes in recurrent EC patients. Abstract : Supplemental Digital Content is available in the text